Functionality of Root-Associated Bacteria along a Salt Marsh Primary Succession - Wang, Miao; Li, Erqin; Liu, Chen; Jousset, Alexandre; Salles, Joana F. (Frontiers in Microbiology, 2017)
Plant-associated bacteria are known for their high functional trait diversity, from which many are likely to play a role in primary and secondary succession, facilitating plant establishment in suboptimal soils conditions. Here we used an undisturbed salt marsh chronosequence that represents over 100 years of soil development to assess how the functional traits of plant associated bacteria respond to soil type, plant species and plant compartment. We isolated and characterized 808 bacterial colonies from the rhizosphere soil and root endosphere of two salt marsh plants, Limonium vulgare and Artemesia maritima, along the chronosequence. From these, a set of 59 strains (with unique BOX-PCR patterns, 16S rRNA sequence and unique to one of the treatments) were further screened for their plant growth promoting traits (siderophore production, IAA production, exoprotease production and biofilm formation), traits associated with bacterial fitness (antibiotic and abiotic stress resistance – pH, osmotic and oxidative stress, and salinity) and metabolic potential. An overall view of functional diversity (multivariate analysis) indicated that the distributional pattern of bacterial functional traits was driven by soil type. Samples from the late succession (Stage 105 year) showed the most restricted distribution , harboring strains with relatively low functionalities, whereas the isolates from intermediate stage (35 year) showed a broad functional profiles. However, strains with high trait performance were largely from stage 65 year. Grouping the traits according to category revealed that the functionality of plant endophytes did not vary along the succession, thus being driven by plant rather than soil type. In opposition, the functionality of rhizosphere isolates responded strongly to variations in soil type as observed for antibiotic resistance (P=0.014). Specifically, certain Pseudomonas sp. and Serratia sp. strains revealed high resistance against abiotic stress and antibiotics and produce more siderophores, confirming the high plant-growth promoting activity of these two genera. Overall, this study contributes to a better understanding of the functional diversity and adaptation of the microbiome at typical salt marsh plant species across soil types. Specifically, soil type was influential only in the rhizosphere but not on the endosphere, indicating a strong plant-driven effect on the functionality of endophytes.